2020
DOI: 10.29244/jam.8.2.129-140
|View full text |Cite
|
Sign up to set email alerts
|

Perbankan Syariah dan Pertumbuhan Ekonomi Indonesia: Bagaimana Kontribusinya?

Abstract: Islamic banking takes part in the Indonesian economic and financial system which contributes to the dynamics of eeconomic growth. The number of Islamic banks in Indonesia, through its market share, is still quite small, namely 5.95% in 2019 of the total national banking market share. One of the main activities of Islamic banking is channeling financing through financing based on the type of use and business category. This study aims to determine the short-term and long-term contribution of Islamic banking to I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 13 publications
1
4
0
3
Order By: Relevance
“…This thing signifies that Islamic bank financing yet capable give of contributing to the economy in Indonesia. Research results from this are in line with research conducted by Widyastuti & Arinta (2020) and Afandi & Amin (2019), which concludes that financing banking for working capital and financing investment does not influence the growth Indonesian economy. However different from the results study conducted by El Ayyubi et al ( 2017) and Setiawan (2019) that financing Islamic banking is an influential positive to the growth economy.…”
Section: Long-term Estimate and Short-term Estimation Resultssupporting
confidence: 85%
See 1 more Smart Citation
“…This thing signifies that Islamic bank financing yet capable give of contributing to the economy in Indonesia. Research results from this are in line with research conducted by Widyastuti & Arinta (2020) and Afandi & Amin (2019), which concludes that financing banking for working capital and financing investment does not influence the growth Indonesian economy. However different from the results study conducted by El Ayyubi et al ( 2017) and Setiawan (2019) that financing Islamic banking is an influential positive to the growth economy.…”
Section: Long-term Estimate and Short-term Estimation Resultssupporting
confidence: 85%
“…This is also consistent with the findings of Setiawan (2019) and Iryanto et al (2020), who found that Sharia bank financing boosts economic growth. However, Widyastuti & Arinta (2020) found that Sharia bank financing for consumption, working capital, and investment had a negative effect on Indonesia's economic growth.…”
Section: Long-term Estimate and Short-term Estimation Resultsmentioning
confidence: 99%
“…Sistem program finansial dilakukan dengan perantara lembaga keuangan terstruktur yakni bank pembangunan, bank sentral, bank umum serta lembaga bukan bank (LBB) yang dimanfaatkan dalam menghimpun dan mengolah dana masyarakat. Salah satu langkah untuk meningkatkan ekonomi yaitu dengan melalui perbankan (Ali & Lubis, 2017;Firmansyah & Utami, 2022;Simatupang, 2019;Widyastuti & Nena Arinta, 2020). Industri perbankan telah berkembang hingga menjadi kebutuhan dasar bagi penduduk negara maju untuk memiliki Bank (Hirmawan, 2015;A.…”
Section: Pendahuluanunclassified
“…Financing disbursed by Islamic banking includes operational funds financing, acquisition financing, and consumer financing, with the amount increasing every year (Emy Widyastuti & Nena Arinta, 2020).…”
Section: 2mentioning
confidence: 99%